Understanding "The Character Building" at Nahdlatul Ulama University Blitar - Arif Muzayin Arif Muzayin Shofwan; Miftakhul Rohman; Choirul Hidayah (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
Nahdlatul Ulama University Blitar has the motto The Character Building in carrying out its vision, mission, and institutional goals. This qualitative descriptive writing with literature study will try to interpret the motto. The data analysis technique uses content analysis by sorting out data according to the objectives and problems studied. This paper finds the following points. First, the academic community of Nahdlatul Ulama University Blitar continues to evaluate program activities or policies in realizing its goals, objectives, vision, and mission, as well as trying to increase job satisfaction for structural officials, employees, and employees. Second, the academic community of Nahdlatul Ulama University Blitar continues to improve social competence for their academics with various activities through the tri dharma of higher education which includes education/teaching, research, and community service. Third, the academic community of Nahdlatul Ulama University Blitar continues to improve morality for their academic community, to practice the teachings of Ahlus Sunnah wal Jamaah an-Naahdliyah in carrying out the Tridharma of Higher Education.